Wagon bridges of the Eastern Cape, c. 1840 "“ 1900: the contribution of engineering to infrastructural development - Walters, Dennis Evelyn (Rhodes University, Faculty of Humanities, Department of History, 2018)
This thesis examines an aspect of economic and technological history which has been little explored in South African history. It argues that the military subjugation and the economic development of the Cape Colony, and particularly of the Eastern Cape, were contingent upon good transportation. The geography of the country, which included relatively impassable mountains and numerous often flooded rivers, necessitated bridges as well as roads. Both were expensive. As a leader in industrial technology, Britain was well placed to extend bridge-building skills to its colonies. This thesis examines the processes by which a small and undeveloped colony strove to create an efficient technological infrastructure. As wagon traffic increased through progress, delays in crossing rivers became a hindrance leading to agitation for bridges. It will be shown that the construction of wagon bridges over the numerous rivers encountered in the Eastern Cape Colony was imperative for the initial free flow of military forces and for later commercial expansion as new towns were established. The eastward expansion was led by the military during the frontier wars followed by the Royal Engineers who built roads and bridges along the eastern frontier. The new Colonial Secretary John Montagu, who arrived in 1843, boosted the colonial finances by overhauling the administration. He established the Central Road Board, an organisation that would drive the building of mountain passes, roads and bridges. The Public Works Department succeeded the Central Road Board and with the financial intervention of the Crown Agents for the Colonies, carried on with an extensive programme of road and bridge building. From the 1870s wagon bridge building lagged behind the huge railway building enterprise in response to the opening up of the diamond and gold mines. The final quarter of the 19th century saw increased bridge building activity in the Eastern Cape with the construction of many iron lattice girder, stone masonry arch and timber trestle bridges. The surviving bridges remain as mute testimony to the skill and expertise of British engineers such as Lewis, Woodifield, Robinson, Fforde, Wakefield, Berkley, Grier, Newey, Westhoven and others.
Keywords: Bridges Design and construction 19th century; Civil engineers -- South Africa Cape of Good Hope; Great Britain. Crown Agents' Office; Public works Great Britain Colonies; Wagon trains -- South Africa Cape of Good Hope